2019
DOI: 10.3928/1081597x-20190930-01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FDA-Reported Visual and Refractive Outcomes of the Toric ICL Lens, SMILE, and Topography-Guided LASIK for the Correction of Myopia and Myopic Astigmatism

Abstract: PURPOSE: To compare U.S. Food and Drug Administration (FDA)–reported visual and refractive outcomes following surgical correction of myopia and myopic astigmatism using the Visian Toric Implantable Collamer Lens (STAAR Surgical, Monrovia, CA) (Toric ICL), small incision lenticule extraction (SMILE), and topography-guided laser in situ keratomileusis (TG-LASIK). METHODS: FDA summary of safety and effectiveness data (SSED) were analyzed for each of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…The current study found no signi cant differences in postoperative UDVA or CDVA among SMILE, WFO and TCAT groups, showing that the three procedures were comparably effective and safe. The majority of previous studies demonstrated the similar results [9][10][11][12][13][14] . A randomized, paired-eye study found that SMILE achieved similar results as WFO LASIK in terms of e cacy index (0.97±0.20 vs. 0.99±0.20; P = 0.56), UDVA of 20/40 or better (100% vs. 100%; P = 1.0), and UDVA of 20/20 or better (84% vs. 87%; P = 0.63) 9 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The current study found no signi cant differences in postoperative UDVA or CDVA among SMILE, WFO and TCAT groups, showing that the three procedures were comparably effective and safe. The majority of previous studies demonstrated the similar results [9][10][11][12][13][14] . A randomized, paired-eye study found that SMILE achieved similar results as WFO LASIK in terms of e cacy index (0.97±0.20 vs. 0.99±0.20; P = 0.56), UDVA of 20/40 or better (100% vs. 100%; P = 1.0), and UDVA of 20/20 or better (84% vs. 87%; P = 0.63) 9 .…”
Section: Discussionsupporting
confidence: 65%
“…The present study found that postoperative MRSE at 1 and 6 months was similar among the three groups, but the 1-month postoperative cylinder was signi cantly different among the three groups, with the highest mean value in the TCAT group. Most previous studies showed comparable refractive results between SMILE and WFO FS-LASIK or SMILE and TCAT FS-LASIK [9][10][11][12][13][14] . The high residual cylinder in the TCAT group of the present study was similar to our previous study 16 , which might be caused by the compensation method for TCAT design.…”
Section: Discussionmentioning
confidence: 82%
“…Concerning predictability, Pedersen et al (17) determined that 78% and 90% of eyes were within ±0.50 and ±1.00 D at 3 years post-SMILE (mean SE of −7.30 D). In order to prevent under-correction, Burazovitch et al (18) employed an 8% correction factor and found that 87% (100%) of eyes were within ±0.50 D (±1.00 D) (mean SE of−7.59 D) of refraction error, while Moshirfar et al (19) found that in their experience, 100% of eyes that had undergone SMILE were within ±0.50 D, relative to just 66% of Toric implantable Collamer lens (ICL)-treated eyes (mean SE > −10.0 D). This led the authors to conclude that SMILE is superior to Toric ICL, although it is important to note that the SMILE group in this study was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…This is good for our profession, but, most importantly, for our patients. Now more than ever, we have techniques and technology to provide safe and highly effective refractive surgery to the majority of patients for most refractive errors, [2][3][4] and increasingly effective strategies to repair unwanted outcomes when they do occur. 5,6 Since initial reports of coronavirus being found in tears and potentially transmissible via the conjunctiva, the risk of coronavirus transmission through ocular surgery has been evaluated.…”
Section: E D I T O R I a Lmentioning
confidence: 99%